The Women’s Struggles in Breaking Gender Inequality in “Enola Holmes” Movie and Its Contribution to the Introduction of Literature Course (Undergraduate Conference on Applied Linguistics, Linguistics, and Literature, 2022)
This study focuses on feminist cases that happened in the world related to the Enola Holmes movie. The objectives of this study are to describe the types of gender inequalities and the struggle of women/feminists in breaking gender inequality in the Enola Holmes movie and relate it to the Introduction of Literature course. The research method used in this study is a qualitative descriptive method with the document analysis instrument using feminist analysis theory by Madsen to conduct research. The result findings of this study indicate several gender inequalities in Enola Holmes movie, which are inequality in getting the right to vote; violence, oppression, and sexual harassment of women; women must obey all the orders of men; freedom of expression is limited by societal standards. Also, the struggles carried out by women/feminists in breaking gender inequality namely, struggle to get voting rights/women's suffrage; struggle for equal education; complementing women's political representation; fighting perpetrators of violence and harassment; struggle for getting freedom of expression. Last, the research findings also found the contribution of this research to the Introduction of Literature course, the results of this feminist analysis can be used to expand knowledge in historical, political, and socio-cultural literacy. This movie can also be used as media and learning materials for the Introduction of Literature course.
Keywords: feminism, women, gender inequality, movie, enola holmes